Protective put strategy for financial investments. - Goh, Jeffrey Chia Fook. (2008)
The objectives in this study are to focus on selecting the optimal insurance level when employing a protective put strategy; investigate how the different factors in this strategy will affect the portfolio performance; and a comparison between the insured portfolio, an uninsured portfolio and an uninsured portfolio in the market.